2015
DOI: 10.1017/s0033291715000744
|View full text |Cite
|
Sign up to set email alerts
|

Parental history of psychiatric diagnoses and unipolar depression: a Danish National Register-based cohort study

Abstract: Background Depression is known to run in families, but the effects of parental history of other psychiatric diagnoses on depression rates are less well studied. Few studies have examined the impact of parental psychopathology on depression rates in older age groups. Methods We established a population-based cohort including all individuals born in Denmark after 1954 and alive on their 10th birthday (N=2,976,264). Exposure variables were maternal and paternal history of schizophrenia, bipolar disorder, depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“… 2 , 3 Depression often first manifests in adolescence 4 , 5 , 6 and, thereafter, individual trajectories of depressive symptoms vary substantially. 7 A family history of depression and an early age at onset are each associated with a more chronic symptom course in adults with MDD, 8 , 9 , 10 but it is not known what shapes early depression trajectories in youth.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 Depression often first manifests in adolescence 4 , 5 , 6 and, thereafter, individual trajectories of depressive symptoms vary substantially. 7 A family history of depression and an early age at onset are each associated with a more chronic symptom course in adults with MDD, 8 , 9 , 10 but it is not known what shapes early depression trajectories in youth.…”
Section: Introductionmentioning
confidence: 99%
“…Many are small, containing few fathers, and their findings are inconsistent. [7][8][9][10][11][12] Some larger studies exist, but they either assess depression retrospectively 13 or use routine clinical data, 14 so are susceptible to recall and ascertainment bias. The only large prospective study that adjusted for maternal depression and did not rely on clinical data found no association between antenatal depression in fathers and adolescent depression at age 18 years.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of MDD occurs before age of 40 years in about 50 percent of patients (7). There have been suggested that etiology, manifestation, and course of depression differ according to the age of onset; compared to later onset, earlier age at onset of MDD is associated with higher genetic loading, atypical symptoms, more irritability and anxiety, personality disorder, alcohol abuse, higher possibility of conversion to bipolar disorder, and poorer long-term outcome (7)(8)(9). Moreover, previous studies have consistently reported an increased suicidal risk in those with early onset (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%